ANALISIS KUALITAS LAYANAN E-COMMERCE MENGGUNAKAN METODE ZONE OF TOLERANCE - Siti Fatonah; Kusrini Kusrini; Asro Nasiri (Informasi Interaktif, 2018)
The quality of e-commerce website services must be considered because it affects the number of users who access the website and decide to buy on an e-commerce website. Shopee is one of the fast-growing e-commerce websites in Indonesia, YLKI received 101 complaints in online shopping including among them complaints from Shopee consumers. The purpose of this study is to analyze the quality of e-commerce website services based on the user's point of view and know the attributes that affect customer satisfaction on service quality based on E-Servqual dimensions, namely efficiency, availability, fulfillment, privacy, responsiveness, compensation and contacts using Zone of Tolerance methods. Data obtained from questionnaires using purposive sampling technique with the number of respondents as many as 100 respondents, then the results of the questionnaire were analyzed using the ZOT method to find out the quality of acceptable minimal services. The results of this study indicate that customers are not satisfied with the quality of service provided with priority improvements to the attributes of Shopee parties willing to bear all shipping costs in the event of a mechanism to replace goods due to Shopee's fault.   Keywords: service quality, e-servqual, ZOT.